Comparing antibiotic prescribing patterns for hidradenitis suppurativa between dermatology and non‐dermatology ambulatory providers - Hannah Tolson; Robin Kikuchi; Rebecca K. Yamamoto; Kaviyon Sadrolashrafi; Lily Guo; Audrey Hao; Sara Bilimoria; Danielle Yee; April W. Armstrong (Wiley, 2024)
Abstract Background Oral antibiotics are a mainstay of treatment for hidradenitis suppurativa (HS) primarily due to their anti‐inflammatory and anti‐microbial properties. Because antibiotics are frequently prescribed to treat HS, concerns exist regarding antibiotic stewardship. There is a paucity of literature comparing how antibiotic prescribing patterns for HS differ between dermatology and non‐dermatology clinicians in the ambulatory setting. Objective This study aims to compare the antibiotic prescribing patterns of dermatology versus non‐dermatology clinicians treating HS in the ambulatory setting. Methods We utilised the National Ambulatory Medical Care Survey (NAMCS) to identify visits for HS patients from 2005 to 2016. We performed multivariate logistic regression analysis to compare the likelihood of prescribing (1) antibiotics and (2) tetracyclines between dermatology and non‐dermatology clinicians in the ambulatory setting. Results We identified a total of 2 424 125 (weighted) HS visits. Approximately 28.0% of visits were conducted by dermatology clinicians, while 72.0% were conducted by non‐dermatology clinicians. Antibiotics were prescribed in 51.9% of visits. Tetracyclines were the most commonly prescribed antibiotics among visits with dermatology clinicians (33.4%), while penicillins/cephalosporins were the most commonly prescribed antibiotic among visits with non‐dermatology clinicians (14.9%). Multivariate logistic regression analysis demonstrated no difference in the overall likelihood of prescribing antibiotic therapy between dermatology and non‐dermatology clinicians (p = 0.35). However, dermatology clinicians were significantly more likely to prescribe tetracyclines than non‐dermatology clinicians (OR 5.48, 95% CI 1.19-25.26, p = 0.03). Conclusion In conclusion, dermatology clinicians were significantly more likely to prescribe tetracyclines than non‐dermatology clinicians for HS patient visits.